Structural Insight Into Ryanodine Receptor Channelopathies - Hadiatullah, Hadiatullah; He, Zhao; Yuchi, Zhiguang (Frontiers in Pharmacology, 2022)
The ryanodine receptors (RyRs) are large cation-selective ligand-gated channels that are expressed in the sarcoplasmic reticulum (SR) membrane. They mediate the controlled release of Ca2+ from SR and play an important role in many cellular processes. The mutations in RyRs are associated with several skeletal muscle and cardiac conditions, including malignant hyperthermia (MH), central core disease (CCD), catecholaminergic polymorphic ventricular tachycardia (CPVT), and arrhythmogenic right ventricular dysplasia (ARVD). Recent breakthroughs in structural biology including cryo-electron microscopy (EM) and X-ray crystallography allowed the determination of a number of near-atomic structures of RyRs, including wildtype and mutant structures as well as the structures in complex with different modulating molecules. This allows us to comprehend the physiological gating and regulatory mechanisms of RyRs and the underlying pathological mechanisms of the disease-causing mutations. In this review, based on the insights gained from the available high-resolution structures of RyRs, we address several questions: 1) what are the gating mechanisms of different RyR isoforms; 2) how RyRs are regulated by multiple channel modulators, including ions, small molecules, and regulatory proteins; 3) how do disease-causing mutations affect the structure and function of RyRs; 4) how can these structural information aid in the diagnosis of the related diseases and the development of pharmacological therapies.